Diazepam Withdrawal Expression is related to Hippocampal NOS-1 Upregulation - Villarmois, Emilce Artur de la; Constantin, María Florencia; Bregonzio, Claudia; Pérez, Mariela Fernanda (Archives of Pharmacy and Pharmaceutical Sciences, 2018)
Background: Benzodiazepines are usually prescribed for anxiety and sleep disorders in a long-term fashion that may cause drug dependence. Discontinuation after prolonged administration may lead to withdrawal expression, being anxiety the most predominant sign. It has been described that a context-dependent associative learning process underlies diazepam dependence. Nitric oxide is a crucial player in learning and memory processes, hippocampal transmission, as well as in benzodiazepines withdrawal. Considering that previous results from our laboratory showed an increase in hippocampal functional plasticity only in diazepam dependent rats, the aim of the present investigation is to determine whether diazepam dependence could alter neuronal nitric oxide synthase enzyme (NOS-1) expression within the hippocampus, by using western blot. Results: chronic diazepam-treated animals that developed dependence showed increase in NOS-1 expression in dorsal, but not in ventral hippocampus, while no-dependent or control animals presented similar NOS-1 protein levels. Conclusion: withdrawal from long-term diazepam exposure could be associated to increased nitric oxide neurotransmission within dorsal hippocampus induced by NOS-1 over-expression. This mechanism could underlie the improved hippocampal synaptic transmission previously observed in diazepam withdrawn animals. Confirmatory experiments need to be addressed to determine the mechanisms by which nitric oxide participates in benzodiazepines withdrawal in order find new molecular targets to develop pharmacological tools to prevent the withdrawal syndrome.